THE DEVELOPMENT OF DIGITAL MEDIA REFLECTS THE ISSUE OF PET RELEASE AT PURANAWAT TEMPLE, BANGKOK - Chaiwanarom, Paweena; Krourat, Bovan (Journal of Buddhist Anthropology, 2023)
Background and Objectives: Pets left at the temple to become stray animals have long been a source of distress for the Puranawat temple. The objectives of this research are to develop digital media innovations that would reflect the issues of bringing pets to release in the Puranawat temple and assess the satisfaction of using digital media. According to the study, this media is intended to be utilized as a tool for preventing problems at their root source, that is, raising public awareness for the public from allowing pet owners to release their animals. So those forsaken animals gradually can decrease until they vanish altogether. Methodology: This research was a mixed method based on community participation building to address the underlying root causes of the stray animal problem at the temple. Three key informants who provided qualitative information through interviews were two persons chosen inside the temple based on purposive selection and an outsider was chosen by accidental selection. After seeing the designed digital media, purposive selected 360 pet owners responded to a satisfaction questionnaire for quantitative data. To assess the statistical findings, the mean (𝑥̅) and standard deviation (S.D.) were utilized. Main Results: A digital media called "Dog - cat problems at Puranawat temple" with a duration of 3.21 minutes was produced as an innovation of this research. Three characters who directly suffered from stray animals in the temple: a monk, a temple staff, and an outsider who came to participate in temple activities provided the narrative of the media with their issues and thoughts. The sample group's evaluation results showed a high level of satisfaction with the generated digital media, with a mean of 4.35 and a standard deviation of 0.70. The topic that received the most in evaluation results was the samples' agreement with the usage of this digital media as a tool to portray the issue of bringing pets to release inside the temple. Involvement to Buddhadhamma: Information technology has been used to build digital media as an innovation in this research that corresponds to the specific requirements of the temple. It indicates that Buddhism responds so well to changing global circumstances. Finally, people who are aware of their responsibility for religious places and public areas will contribute to the sustainable advancement of Buddhism and society. Conclusions: The innovation of this research was a digital media named "Dog - cat problems at Puranawat temple" that had garnered positive cooperation from all parties involved. The sample group that viewed the media concurred with the usage of this digital media as a tool to reflect the issue of pet abandonment in the temple. Media raised awareness among viewers of their social effects. The designed media could have been an effective tool in a campaign to stop releasing pets into Puranawat temple. Furthermore, temples or other public places that experienced similar issues could use this digital media as a model for developing new improvements in the future based on the environment of each venue.